A Retrospective Study Using the String of Pearls Tibial Plateau Levelling Osteotomy Locking Plate for the Treatment of Cranial Cruciate Ligament Disease - McGregor, Ross E.; Buffa, Eugene A.; Tan, Christopher J.; Schembri, Mark A.; Badcock, Caro-Anne; Lai, Alen (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to describe the use of String of Pearls (SOP) tibial plateau levelling osteotomy (TPLO) locking plates for the treatment of cranial cruciate ligament disease and retrospectively assess osteotomy healing, tibial plateau angle (TPA) change (c) and overall complication rates.Methods Medical records and radiographic studies of 170 SOP TPLO surgical procedures were analysed. Radiographic measurement of TPAc and osteotomy union was determined 6 to 8 weeks postoperatively. Intra- and postoperative major and minor complications were identified. Factors influencing TPAc, osteotomy union and complications were assessed.Results Mean (standard deviation) TPAc was 1.3° (1.61) and median osteotomy union was graded as 2 (26–50%) union. Improved osteotomy union was associated with retention of the antirotational pin (odds ratio [OR]: 2.3; 95% confidence interval [CI]: 1.3–4; p = 0.005) and reduced TPAc (OR: 0.8; 95%CI: 0.66–0.97; p = 0.02). Complications occurred in 42 (24.7%) procedures with 11 (6.5%) considered major and 31 (18.2%) minor.Clinical significance The use of the SOP TPLO plating system resulted in a median grade 2 (26–50%) radiographic osteotomy union score at 6 to 8 weeks' follow-up, less than previous TPLO locking plate studies. Osteotomy union was associated with retention of the antirotational pin and reduced TPAc. Major and minor complication rates were marginally greater than recent locking plate studies with fibular fracture and screw loosening common complications. The use of SOP TPLO plates is cautioned and further study is warranted.
Keywords: tibial plateau levelling osteotomy; String of Pearls; cruciate ligament disease; osteotomy healing; complications